THE SCIENCE OF SPORT Swiming - Alexander, Marinof; Coumbe-Lilley, John (The science of sport, 2016)
The Science of Sport - Swimming is a complete guide for swimming training through the application of physiological, biomechanical, psychological, strength and conditioning, nutritional and injury management methods that can be used to optimize performance. Practical examples are included on the components of swimming conditioning, technical and mental training, and how they relate to the various swimming speciality events. The text provides details on mental and strength conditioning training exercises and racing day preparation methods for various abilities, including speciality swimmers who seek performance improvement constantly. The book includes contributions from leading coaches and sport scientists, sport psychologists, sports medical practitioners and Olympic, world and national champion swimmers.